Development of Islamic Values-Integrated E-Module in Plane Shapes for Grade V Elementary School Students - Ayudi Ningrum, Ajeng; Hadikusuma Ramadan, Zaka (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper reports a development research of an integrated Islamic values mathematics E-Module on the plane shapes material for grade V elementary school using the limited ADDIE model (Analysis, Design, Development). The analysis stage identifies learning problems through interviewing the teacher. In the design, the E-Module was designed in Canva and converted into a flip-book via Heyzine. Development involved validation by six experts (two material experts, two language experts, and two design experts) as well as a small-scale trial with one teacher and ten students. Data were collected through structured interviews and validation sheets, and analysed qualitatively and quantitatively. The expert validation results indicated very high feasibility, consisting of 95.25% material experts, 90% language experts, and 93.5% design experts (average 93%). The responses of teachers (83.3%) and students (84.6%) also met the criteria of